Chura Narykov is a Politician of the Kazan Khanate - Mukhametzianova L.Kh. (Золотоордынское обозрение)
Research objectives: To reconstruct the image of Chura, the son of Naryk (Chura Narykov) – a political figure and historical personality of the period of the Kazan Khanate – based on a comparison of the historical epic with the history of the Tatar khanates in the first half of sixteenth century. Research materials: The author analyzes various historical sources and literature with information about the real personality of Chura Narykov, his life, and his work. She focuses on the history of the Kazan Khanate in the sixteenth century and analyzes the texts of dastans collected and published by Russian and foreign scholars from the second half of nineteenth century, along with archival and published epic texts in various versions dedicated to Chura Batyr which were distributed and recorded by Tatar-speaking informants in the Volga region. In turn, information about Chura Narykov as a real person is contained in Russian chronicles, the anonymous “Kazan history” of the sixteenth century, and in publications of Kh. Atlasi (1993), R. Fakhretdin (1995), M. Khudyakov (1990), A.Kh. Khalikov (1992), D.M. Iskhakov (1994, 1997, 2017), S.Kh. Alishev (1995), A.-Z. Validi (1992), and others. Results and novelty of the research: The author draws parallels between historical reality and the epic Chura-batyr, addresses the problems of the historical explanation of the rich material of folk art, and reveals the commonality between reality and epic works about Chura-batyr. The study systematically proves the relevance – in the history of the Turkic peoples – of political events associated with the Tatar khanates that existed until the late Middle Ages, focusing on the fact that during this period Kazan was a major political center of important events of a global scale. Key aspects of the topic raised in the study contribute to a more detailed study of the history of the Golden Horde and the Tatar khanates, determining the role and historical significance of the Tatar version of the dastan about Chura-batyr along with other Turkic versions and variants. The historical personality of Chura Narykov is considered as a prototype of not only the Tatar, but also the Turkic historical and heroic epic.